2012
DOI: 10.4049/jimmunol.1103698
|View full text |Cite
|
Sign up to set email alerts
|

Selective Blockade of Herpesvirus Entry Mediator–B and T Lymphocyte Attenuator Pathway Ameliorates Acute Graft-versus-Host Reaction

Abstract: The cosignaling network mediated by the herpesvirus entry mediator (HVEM; TNFRSF14) functions as a dual directional system that involves proinflammatory ligand, lymphotoxin that exhibits inducible expression and competes with HSV glycoprotein D for HVEM, a receptor expressed by T lymphocytes (LIGHT; TNFSF14), and the inhibitory Ig family member B and T lymphocyte attenuator (BTLA). To dissect the differential contributions of HVEM/BTLA and HVEM/LIGHT interactions, topographically-specific, competitive, and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…Judging from recent reports (11Y16, 24), the strategy engaging the co-inhibitory pathway may improve allograft survival. Especially, selective BTLA/HVEM blockage, not LIGHT, in graft-versus-host reaction decreased the functional activity of the alloreactive T cells (25). These above reports indicated that the control of BTLA/HVEM/LIGHT pathway may ameliorate alloimmune responses.…”
Section: Discussionmentioning
confidence: 93%
“…Judging from recent reports (11Y16, 24), the strategy engaging the co-inhibitory pathway may improve allograft survival. Especially, selective BTLA/HVEM blockage, not LIGHT, in graft-versus-host reaction decreased the functional activity of the alloreactive T cells (25). These above reports indicated that the control of BTLA/HVEM/LIGHT pathway may ameliorate alloimmune responses.…”
Section: Discussionmentioning
confidence: 93%
“…Representative sections (spaced 50 m apart) throughout the TG were fixed for 2 h in 4% paraformaldehyde at 4°C, followed by a 30-min incubation in Dako Serum-Free Protein Block. Rat anti-mouse HVEM clone 10F3 antibody (46) was incubated in protein block at 4°C overnight. After three rinses for 5 min each in 1ϫ phosphate-buffered saline (PBS), slides were incubated for 1 h at 25°C with secondary antibody labeled with Alexa Fluor-488 (green) (Invitrogen, Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
“…GVHD is an immunologic syndrome affecting transplant recipients in which engrafted donor T cells attack host tissues, causing rampant damage (140). Investigators have had success in decreasing symptoms of GVHD in mice by targeting both BTLA-HVEM and LIGHT-HVEM interactions with blocking antibodies (137)(138)(139). Blockade of LIGHT-HVEM signaling has also been shown to increase the rate of survival of solid allografts, including pancreatic islets and cardiac transplants (141,142).…”
Section: Hvem Signaling Impacts a Variety Of Human Diseases Offeringmentioning
confidence: 99%
“…However, HVEM is implicated in a wide range of autoimmune, inflammatory, and infectious processes that impact an astonishing diversity of human syndromes (24). Because of this, the HVEM signaling network is a rich area of research for the discovery of new therapies.Levels of soluble HVEM are elevated in the sera of patients with allergic asthma, rheumatoid arthritis (RA), and atopic dermatitis (135), but HVEM/LIGHT/BTLA signaling and therapeutic opportunities within that network have been most extensively studied in models of graft-versus-host disease (GVHD) (64,74,(136)(137)(138)(139). GVHD is an immunologic syndrome affecting transplant recipients in which engrafted donor T cells attack host tissues, causing rampant damage (140).…”
mentioning
confidence: 99%